SELF-REGULATED LEARNING DAN PROKRASTINASI: STUDI PADA SISWA SMK PANCA KARYA TANGERANG - Nuryetty Zain; Susi Setya Wahyuni (Faculty of Economics, State University of Jakarta., 2015)
This research aims to know whether there is the correlation between self-regulated learning and procrastination in Students of SMK Panca Karya Tangerang. Research method used is a method of survey. The population in this research was all of the students in SMK Panca Karya Tangerang, affordable population in this research is all of Office Administration’s students which consisted of 112 students, and sample used as many as 94 students by using techniques proportional random sampling. An instrument used to obtain data for variable x (self-regulated learning) and variable y (procrastination) measured using a questionnaire with Liker’s Scale.This study uses the logistic correlation hypothesis test.Results of the analysis showed thatthere is a negative and significant correlation between Self-Regulated Learning and Procrastination.